Evaluation of nanotoxicity of Araucaria heterophylla gum derived green synthesized silver nanoparticles on Eudrilus eugeniae and Danio rerio - Samrot, Antony V.; C., SaiPriya; J., Lavanya Agnes Angalene; S. M., Roshini; P. J., Jane Cypriyana; S., Saigeetha; P., Raji; Subbiah, Suresh Kumar (Springer, 2019)
Metal nanoparticles found its application in most fields because of its different physiochemical properties. Although there are several methods for synthesis of nanoparticles, where green and biological synthesis of nanoparticles reduces the toxicity. These metal nanoparticles are not properly disposed to the environment. Thus, this study was focussed to evaluate the effects of Araucaria heterophylla mediated green synthesised silver nanoparticles on various in vivo models such as earth worm—Eudrilus eugeniae and zebra fish—Danio rerio. Even the biologically synthesised nanoparticles were showing negative impacts on these models. Silver nanoparticles was found to cause epithelial erosion and lipofucshin deposits on Eudrilus eugeniae, where it was causing erosion and structure deformation in guts of Danio rerio.